Insulin resistance and hepatitis C: an evolving story. Issue 8 (19th January 2011) - Eslam, Mohammed; Khattab, Mahmoud AboElneen; Harrison, Stephen A
Abstract : Insulin resistance and diabetes are inextricably linked to chronic hepatitis C. Our understanding of this relationship continues to improve. This review focuses on the molecular mechanisms relating insulin resistance to hepatitis C with a subsequent overview of the consequences of hepatitis C-associated insulin resistance and diabetes, as well as perspectives for future management.